PROTOKOL KULTUR EMBRIO SIGOTIK KELAPA KOPYOR - sukedah, sukedah; Djajanegara, Ira N.; Makhziah, Makhziah (Badan Pengkajian dan Penerapan Teknologi, 2006)
In effort to get the true-to-type “Kopyor” coconut (matured coconut with broken meat particles due to abnormal formation of endosperm), the only way is inoculate the embryo in synthetic media under in vitro condition. A protocol of coconut embryo culture was established for “Kopyor” coconut grown in East Java through testing a number of media protocols and adding auxin IBA for rooting. The media protocols tested consisted of Y3 (Eeuwens) and MS (Murashige & Skoog) basal media, i.e. Protocol I (UPLB/Philippiness) as a control, Protocol II with a series of solid media Y3 (solid Y3 in germinating phase; solid Y3 in subculture I,II,III and solid Y3 in subculture IV), Protocol III with a series of solid media Y3 in germinating phase; solid Y3 in subculture I,II,III ; and liquid Y3 in subculture IV, Protocol IV with a series of solid media MS (solid MS in germinating phase; solid MS in subculture I,II,III; solid MS in subculture IV), and Protocol V with a series of liquid media MS in germinating phase; solid Y3 in subculture I,II,III; liquid Y3 in subculture IV. The growth of Kopyor coconut embryo was very fast in media Protocol II (a series of solid media Y3) and forming prefect plantlet higher than others. The alternative protocol that could give a positive result was Protocol III, this protocol showed a plantlet good rooting. Growth regulator IBA could induce primary root of kelapa kopyor plantlets. The effective concentration to stimuli lateral root of kelapa kopyor plantlet was 2 ppm IBA.